2021
DOI: 10.3390/ijerph19010004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Economic Policy Uncertainty on Carbon Emissions: Evidence from 137 Multinational Countries

Abstract: With growing economic policy uncertainty (EPU) and the importance of protecting the natural environment worldwide, the relationship between EPU and carbon emissions should be investigated further. However, conclusions in the existing literature on the relationship between EPU and carbon emission are inconclusive. This paper aims to examine the influence of EPU on carbon emissions according to the Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) model. To investigate such essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 52 publications
1
4
1
Order By: Relevance
“…The results show that the estimated coefficient of laglog_epu is 0.244 and is significantly positive, indicating that when the uncertainty of urban economic policy increases by 1 percentage point, the city's carbon emission intensity will increase by 0.244 tons per 10,000 yuan, which is an increase of 4.28 percentage points compared to the average carbon emission intensity of the city (0.244/5.699 = 0.0428). This result is consistent with Wang et al (2022). Using the crosscountry data for 137 countries from 1970 to 2018, they investigate the impact of economic policy uncertainty on CO 2 emissions and find that EPU would increase CO 2 emissions.…”
Section: Basic Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The results show that the estimated coefficient of laglog_epu is 0.244 and is significantly positive, indicating that when the uncertainty of urban economic policy increases by 1 percentage point, the city's carbon emission intensity will increase by 0.244 tons per 10,000 yuan, which is an increase of 4.28 percentage points compared to the average carbon emission intensity of the city (0.244/5.699 = 0.0428). This result is consistent with Wang et al (2022). Using the crosscountry data for 137 countries from 1970 to 2018, they investigate the impact of economic policy uncertainty on CO 2 emissions and find that EPU would increase CO 2 emissions.…”
Section: Basic Resultssupporting
confidence: 73%
“…This is because the higher the level of economic development, the more willing the city is to pursue high-quality development, and the more capable it is to accelerate the green and low-carbon transformation. Wang et al (2022) find that a higher level of economic development would reduce the environmental adverse effect of EPU. Second, the more industrial enterprises above the designated size, the higher the urban carbon emission intensity.…”
Section: Basic Resultsmentioning
confidence: 86%
“…Obviously, the findings of this paper differ from the empirical findings of Jiang et al [ 15 ], Wang et al [ 17 ], Chen et al [ 18 ], and Liu and Zhang [ 19 ], because we examined the dynamic impact of provincial EPU on carbon emissions in China from a nonlinear perspective, taking into account the complexity and structural differences of the Chinese provincial economic system. The findings are more consistent with Chinese economic reality, which is the paper’s main marginal contribution.…”
Section: Discussioncontrasting
confidence: 73%
“…Similarly, Wang et al [ 16 ] found that US carbon emissions show a positive relationship with EPU. Based on cross-country data, Wang et al [ 17 ] discovered that EPU increases carbon emissions, whereas economic development, globalization, and international trade significantly moderate the carbon emission effects of EPU. By contrast, there are results in the existing literature that contradict the above studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More specifically, consumption and production-based emissions. Understandably, numerous studies have confirmed the relative importance of the STIRPAT model in evaluating the structural relationship between macroeconomic and environmental variables (Koop 1998;Koop and Tole 1999;Yu et al 2021;Wang et al 2022). Furthermore, we utilised data on eighteen (18) industrial economies with reliable EPU data.…”
Section: Introductionmentioning
confidence: 99%